A political history of the Bhacas from earliest times to 1910 - Makaula, Anderson Mhlauli (Rhodes University, Faculty of Humanities, Department of History, 1989)
The Bhacas are people whose history has not yet been clearly written. Unlike the Mpondo, Xhosa and Thempu chiefdoms, the Bhacas are comparatively recent immigrants into the Cape area. The first chapter deals with origins of the Bhacas and introduces the reader to Bhaca affairs. The chiefdom is said to have been a victim of the disruptive Tshakan wars of the early 19th century, and Madzikane, who later on assumed the reputation of being the architect of the Bhaca nation, left Natal seeking a place where to establish his independence. He collected a large number of fugitives scattered in the southern part of Natal and migrated to the Embondzeni Great Place in Mount Frere. The second chapter concentrates on the habits and customs of the Bhacas. The Bhacas of Mount Frere district are divided into two autonomous chiefdoms according to the descendants of Sonyangwe and Ncapayi, sons of the renowned Great Bhaca chief, Madzikane. Bhaca customs are characterised by their First Fruit Festival dialect.(ingcubhe) and their distinctive Thsefula Then comes the era of Ncapayi who had been renowned for his warlike propensities, and the controversial Voortrekker attack of 1840. It was however, during his reign that mission work started amongst the Bhacas. This left an indelible impression among the Bhacas because Osborn Mission Station was established in 1858 during Mamjucu's reign, the widow of Ncapayi, many years after his death . The influence of missionaries coupled with the problems encountered by Makaula, Ncapayi's son from the surrounding chiefdoms, led to the acceptance of colonial rule. This leads us to chapters 6, 7 and 8 where the colonial government interfers in the Bhaca traditional administrative system especially in matters relating to the allocation of land, appointment of headmen, relations between Makaula and Nomtsheketshe and relations between the Bhacas and the Mpondo. It was during Makaula's regime that many denominations were established in the Mount Frere district. A great measure of credit should be given to these churches for placing systematically before the Bhacas the higher standards of belief and conduct. The history of Bhacas from the 1860's was characterised by change and modification due to the increasing contact with the white man's culture.
Keywords: Bhaca (African people); South Africa -- History